2007
DOI: 10.1080/02688690701210562
|View full text |Cite
|
Sign up to set email alerts
|

Transfer times for patients with extradural and subdural haematomas to neurosurgery in Greater Manchester

Abstract: Delay in transfer of patients with acute extradural (EDH) or subdural (SDH) haematoma to definitive neurosurgical evacuation has a detrimental effect on outcome. From July 2003 to December 2005 we undertook a prospective analysis of patients admitted to our unit for neurosurgical evacuation of their haematoma, who were transferred from non-neurosurgical hospitals. Data was collected for: 1) overall transfer time, 2) time taken from injury or deterioration to CT scan, 3) time from CT scan to arrival at our unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…For the past 2 decades, studies have documented a substantial increase in patient mortality and morbidity associated with delays in transfer to an appropriate trauma center for definitive care. This detrimental outcome impact has been observed most significantly in patients who have sustained head injuries in comparison with other mechanisms of injury despite similar intergroup injury severity [8,9]. It would, therefore, seem reasonable to conclude that any further delay caused by obtaining CT examinations before transfer could potentially increase trauma-related morbidity and mortality.…”
Section: Discussionmentioning
confidence: 93%
“…For the past 2 decades, studies have documented a substantial increase in patient mortality and morbidity associated with delays in transfer to an appropriate trauma center for definitive care. This detrimental outcome impact has been observed most significantly in patients who have sustained head injuries in comparison with other mechanisms of injury despite similar intergroup injury severity [8,9]. It would, therefore, seem reasonable to conclude that any further delay caused by obtaining CT examinations before transfer could potentially increase trauma-related morbidity and mortality.…”
Section: Discussionmentioning
confidence: 93%
“…Time from trauma until surgical decompression affects the mortality. Many authors have observed that the sooner surgery is performed in cases of acute head trauma, the better the final results are (6,12,14,16,21,41,46). Seelig et al (32) reported considerable decline in the rates of mortality and morbidity of the patients operated in the first four hours after the trauma compared to those operated upon later.…”
Section: █ Conclusionmentioning
confidence: 99%
“…7 Within the latter, a case has been made for increasing the number of intensive care beds within SNCs to enable them to accept a higher proportion of the patients with TBI referred to them. However, even if this provision were made, the pre-trauma system patterns of carehighlighted in the recent National Confidential Enquiry into Patient Outcome and Death (NCEPOD) report and other publications -would not have allowed patients with TBI injured nearest a NSAH to receive early neurosurgery (within 4 hours of injury 5,8 ).…”
Section: Initial Cost-benefit Estimate For Early Neurosurgerymentioning
confidence: 99%
“…The analysis showed that in 2005-7 patients with SDH/EDH who are taken first to a NSAH are transferred to the neurosurgical centre on average 5-7 hours after injury. 5 This is due to inherent delays of stabilisation for CT/transfer and referral/ acceptance communications. The only means of achieving early neurosurgery is to take all patients with TBI from scene to the nearest SNC, which -excluding the 10% of the UK's population who live in remote and rural areas -is commonly < 1 hour's journey time from the scene of injury.…”
Section: Initial Cost-benefit Estimate For Early Neurosurgerymentioning
confidence: 99%
See 1 more Smart Citation